Assessing the phosphorus demand in European agricultural soils based on the Olsen method - Recena, Ramiro; García-López, Ana M.; Quintero, José M.; Skyttä, Annaliina; Ylivainio, Kari; Santner, Jakob; Buenemann, Else; Delgado, Antonio (Elsevier BV, 2022)
Overcoming the consequences of future scarcity of P is crucial to ensure agriculture sustainability. This requires decision-making processes depending on data on the P status of agricultural fields, commonly conducted with soil P tests (SPTs), and efficient use of the resource on a societal scale following a circular economy approach. All this will decrease the P losses and the subsequent environmental impact. However, SPTs are not universal and, even for a given SPT, the definition of threshold values for fertilizer response is not accurate. This work aimed to define models to predict Olsen P threshold values, allowing the identification of P-responsive sites at the European scale as a basis for more accurate and sustainable P fertilization schemes based on a circular economy approach. To this end, a data set was compiled based on a literature review that describes the Olsen P threshold values for different crops under field conditions. Subsequently, an analysis of potential P fertilizer requirements was performed on agricultural soils of the European Union (EU) using the data set of the LUCAS project and how this need can be covered with a circular economy approach. Environmental factors were more relevant than crops to explain the variation in threshold values. A regression model involving soil pH and clay content and annual average rainfall as independent variables explained 61% of the variance in Olsen P threshold values. When soil pH and clay content were the only explanatory variables, the explained variance was 49%. This reveals the need to take into account factors related to P buffer and sorption capacity to estimate accurate threshold values. We detected that only 27.8% of EU cropland soils and 42.7% of grassland soils were P-responsive. We can conclude that a more precise allocation of the resource is possible in P-responsive sites and also that most of the European demand for P could be covered by recycling P from manure, wastewater, and municipal solid waste.
Keywords: fertilizer; soil phosphorus test; threshold value; Olsen-P; Soil P test; Circular economy